Biomechanical Influences on Mesh-Related Complications in Incisional Hernia Repair - Kallinowski, Friedrich; Ludwig, Yannique; Gutjahr, Dominik; Gerhard, Christian; Schulte-Hörmann, Hannah; Krimmel, Lena; Lesch, Carolin; Uhr, Katharina; Lösel, Philipp; Voß, Samuel; Heuveline, Vincent; Vollmer, Matthias; et al. (Frontiers in Surgery, 2021)
Aim: Hernia repair strengthens the abdominal wall with a textile mesh. Recurrence and pain indicate weak bonds between mesh and tissue. It remains a question which biomechanical factors strengthen the mesh-tissue interface, and whether surgeons can enhance the bond between mesh and tissue. Material and Methods: This study assessed the strength of the mesh-tissue interface by dynamic loads. A self-built bench test delivered dynamic impacts. The test simulated coughing. Porcine and bovine tissue were used for the bench test. Tissue quality, mesh adhesiveness, and fixation intensity influenced the retention power. The influences were condensed in a formula to assess the durability of the repair. The formula was applied to clinical work. The relative strength of reconstruction was related to the individual human abdominal wall. From computerized tomography at rest and during Valsalva's Maneuver, the tissue quality of the individual patient was determined before surgery. Results: The results showed that biomechanical parameters observed in porcine, bovine, and human tissue were in the same range. Tissues failed in distinct patterns. Sutures slackened or burst at vulnerable points. Both the load duration and the peak load increased destruction. Stress concentrations elevated failure rates. Regional areas of force contortions increased stress concentrations. Hernia repair improved strain levels. Measures for improvement included the closure of the defect, use of higher dynamic intermittent strain (DIS) class meshes, increased mesh overlap, and additional fixation. Surgeons chose the safety margin of the reconstruction as desired. Conclusion: The tissue quality has now been introduced into the concept of a critical and a gained resistance toward pressure-related impacts. A durable hernia repair could be designed from available coefficients. Using biomechanical principles, surgeons could minimize pain levels. Mesh-related complications such as hernia recurrence can potentially be avoided in incisional hernia repair.